Development of a knowlege-based decision making system for the selection of walking aided rehabilitation apparatus - Ekanayake R. M. T. C. B. (2008)
This dissertation presents the development of a knowledge based decision support system for the conceptual design of wallung aided rehabilitation apparatus. An artificial neural network is employed for the decision malung process.